Horticultural therapy in greenery design. Example of the "Światło" hospice in Toruń - Rogatka, Krzysztof; Ziemkiewicz, Katarzyna (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The aim of the article is to present the method of horticultural therapy (gardening therapy) and its application in designing green areas using the example of the sensory garden at the "Światło" hospice in Toruń. The issue of horticultural therapy and its use in shaping green areas was raised due to the important role of greenery in human life (e.g. they absorb pollutants, produce oxygen, perform an insulating function) and the growing importance of horticultural therapy in the design of usable areas.
Keywords: horticultural therapy; sensory garden; green areas; city; inhabitants; terapia ogrodnicza; ogród sensoryczny; tereny zielone; miasto; mieszkańcy